How effective are approaches to migrant screening for infectious diseases in Europe? A systematic review. Issue 9 (September 2018) - Seedat, Farah; Hargreaves, Sally; Nellums, Laura B; Ouyang, Jing; Brown, Michael; Friedland, Jon S
Summary: Rates of migration to Europe, and within Europe, have increased in recent years, with considerable implications for health systems. Migrants in Europe face a disproportionate burden of tuberculosis, HIV, and hepatitis B and C, yet experience a large number of barriers to accessing statutory health care on arrival. A better understanding of how to deliver effective and cost-effective screening, vaccination, and health services to this group is now crucial. We did a systematic review to document and assess the effectiveness and cost-effectiveness of approaches used for infectious diseases screening, and to explore facilitators and barriers experienced by migrants to accessing screening programmes. Following PRISMA guidelines, we searched Embase, PubMed, PsychINFO, the Cochrane Library, and Web of Science (1989 to July 1, 2015, updated on Jan 1, 2018), with no language restrictions, and systematically approached experts across the European Union (EU) for grey literature. Inclusion criteria were primary research studies assessing screening interventions for any infectious disease in the migrant (foreign-born) population residing in EU or European Economic Area (EEA) countries. Primary outcomes were the following effectiveness indicators: uptake of screening, coverage, infections detected, and treatment outcomes. Of 4112 unique records, 47 studies met our inclusion criteria, from ten European countries (Belgium, Denmark, France, Italy, the Netherlands, Norway, Spain, Sweden, Switzerland, and the UK) encompassing 248 402 migrants. We found that most European countries screening migrants focus on single diseases only—predominantly active or latent tuberculosis infection—and specifically target asylum seekers and refugees, with 22 studies reporting on other infections (including HIV and hepatitis B and C). An infection was detected in 3·74% (range 0·00–95·16) of migrants. Latent tuberculosis had the highest prevalence across all infections (median 15·02% [0·35–31·81]). Uptake of screening by migrants was high (median 79·50% [18·62–100·00]), particularly in primary health-care settings (uptake 96·77% [76·00–100·00]). However, in 24·62% (0·12–78·99) of migrants screening was not completed and a final diagnosis was not made. Pooled data highlight high treatment completion in migrants (83·79%, range 0·00–100·00), yet data were highly heterogeneous for this outcome, masking important disparities between studies and infections, with only 54·45% (35·71–72·27) of migrants with latent tuberculosis ultimately completing treatment after screening. Coverage of the migrant population in Europe is low (39·29% [14·53–92·50]). Data on cost-effectiveness were scarce, but suggest moderate to high cost-effectiveness of migrant screening programmes depending on migrant group and disease targeted. European countries have adopted a variety of approaches to screening migrants for infections; however, these are limited in scope to single diseases and a narrow subset of migrants, with low coverage. More emphasis must be placed on developing innovative and sustainable strategies to facilitate screening and treatment completion and improve health outcomes, encompassing multiple key infections with consideration given to a wider group of high-risk migrants. Policy makers and researchers involved with global migration need to ensure a longer-term view on improving health outcomes in migrant populations as they integrate into health systems in host countries.